CRIMINAL PROSECUTION OF PERSONS WHO DO NOT SPEAK THE LANGUAGE OF CRIMINAL PROCESS - Hong, Nguyen; Tuyen, Tran; Pushkarev , Viktor; Fadeev , Pavel; Khmelev , Sergey (Revista Inclusiones, 2020)
With the increasing number of foreigners and stateless persons in the sphere of criminal proceedings, there are problems with applying the principle of the language of the criminal process in the pre-trial phase. This article analyzes investigative and court practice and provisions of the current Criminal Procedure Law on the Language of Criminal Process. We also take into consideration the provisions of the European Court of Human Rights. We aim to justify the necessity to adjust several norms of the Russian Code of Criminal Procedure and the Penal Code of the Socialist Republic of Vietnam in order to improve them as well as to increase the quality and effectiveness of criminal prosecution.